PENGARUH EARNING PER SHARE DAN DIVIDEND PER SHARE TERHADAP HARGA SAHAM PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Studi Pada Perusahaan yang Terdaftar di Indeks LQ 45 Periode 2013-2016) - Tri Yuwono; Subagyo Subagyo; Andrea Gideon (CAHAYA AKTIVA, 2019)
This study aims to examine the influence of earning pershare and dividend per share,to the stock price. Thestock price coefficient is measured by the result of regression slope between cummulative abnormal return and unexpected earnings. The population of this study are companies that are listed on LQ 45 Index in 2013-2016. Based on purposive sampling method, the total obtained samples are 17 companies.The source of data are taken from annual reports of companies that are listed on Indonesia stock exchange in 2013-2016. The data analysis method is using multiple linear regression with SPSS 16. software application.The result of this study found that earning per share and devidend per share have significant positive effect to the stock price coefficient partially or simultaneously.Keywords : earning per share, dividend per share, LQ45 index, stock price.